Immunopathological features of rat Staphylococcus aureus arthritis. - Bremell, T (1994)
Staphylococcus aureus is the most common bacterial species found in nongonococcal bacterial arthritis in humans. We present the first description, to our knowledge, of an outbreak of spontaneous staphylococcal arthritis in a rat colony. In a group of 10 rats, 9 displayed arthritis. Clinically, the most obvious findings were arthritis of one or both hindpaws and malaise. Bacteriophage typing showed the common phage type 85 in isolates recovered from the joints, blood, and bedding of rats and from the nose and cheeks of one person from the staff of the animal facility. The S. aureus strain proved to produce staphylococcal enterotoxin A and exhibited strong binding to collagen types I and II and bone sialoprotein, which are potentially important virulence factors. When the recovered S. aureus strain was injected intravenously into healthy rats, severe septic arthritis was induced in almost all of the animals. The arthritic lesions were characterized by infiltration of phagocytic cells and T lymphocytes into the synovium. Many of the synovial cells strongly expressed major histocompatibility complex class II molecules. Increased levels of interleukin 6 in serum as well as a prominent polyclonal B-cell activation were noted throughout the disease course. Pretreatment of S. aureus-injected rats in vivo with an antibody to the alpha beta T-cell receptor significantly decreased the severity of the arthritis. Our results indicate that alpha beta + T lymphocytes contribute to an erosive and persistent course of S. aureus arthritis.